Selective Activity of Chrysin-6-C-Fucopyranoside from Cyclanthera pedata Toward Peroxisome Proliferator-Activated Receptor Gamma - Marco Zuccolo; Angela Bassoli; Gigliola Borgonovo; Luca Giupponi; Annamaria Giorgi; Aniello Schiano Moriello; Fabio Arturo Iannotti (Molecules)
Caigua (Cyclanthera pedata (L.) Schrad.) is a traditional herbal remedy traditionally used in Latin America for its health benefits and to treat metabolic disorders, including diabetes. Despite interest in its herbal use, the phytochemical properties of caigua’s secondary metabolites are poorly known. This study aimed to isolate the main flavone glycosides from the leaves of caigua landrace cultivated in the Camonica Valley (Italy) using flash chromatography and evaluate their potential activity toward peroxisome proliferator-activated receptors (PPARs) and transient receptor potential (TRP) ion channels through luciferase and intracellular calcium assays. We found that the caigua species-specific flavone glycoside, chrysin-6-C-fucopyranoside, showed potent and selective activity toward PPARγ, with no effects on other PPAR subtypes or TRP channels. These findings indicate that the caigua plant could offer a safer alternative to conventional PPARγ agonists, whose use as antidiabetic drugs is limited by severe side effects that currently restrict the clinical use of conventional PPAR agonists.